Dukungan Keluarga dan Perilaku Pengaturan Diet pada Penderita Diabetes Melitus - Margareta H. Nurti; Engelina Nabuasa; Helga J. N. Ndun (Universitas Nusa Cendana, 2019)
Diabetes mellitus (DM) is a chronic disease requiring continuous care and sustainable self-management. It also needs adequate family support to prevent acute complications and reduce chronic complications. The purpose of this study was to analyze the relationship between family support with the dietary management of DM patients in the working area of Pasir Panjang Health Center Kupang City Year 2017. The research method was an analytical survey with a cross-sectional approach. The population in this study was all new cases of diabetes collected from January to July 2017 of which a sample of 53 people selected using a random sampling technique. The results showed that the appreciation support p = 0,000 < p = 0,05, instrumental support p = 0,000 < p = 0,05, informational support p = 0,000 < p = 0,05 and emotional support p = 0,000 < p = 0,05 were associated with the dietary rules behavior of the diet of DM patients. Health center needs to involve the family in health promotion programs related to dietary management for DM patients.